Kajian Yuridis Terhadap Pembatalan Penetapan Anggota DPR RI Terpilih Tahun 2024 Dihubungkan dengan Sistem Pemilu Proporsional Terbuka - Surya Daniel Batara; Wilma Silalahi (Prodi PGSD Unsultra, 2026)
This study examines the legal provisions for the cancellation of the appointment of elected members of the Indonesian House of Representatives (DPR RI) in 2024 from the perspective of the open proportional representation system in Indonesia. The main issue examined is how the mechanism for canceling the appointment of elected candidates is regulated in legislation and its implications for the principles of popular sovereignty, legal certainty, and the legitimacy of election results. This study uses a normative juridical method with a statutory, conceptual, and case-based approach. The legal materials used include Law Number 7 of 2017 concerning Elections, KPU Regulation Number 6 of 2024, Constitutional Court decisions, and various relevant legal literature. The results show that the cancellation of the appointment of elected candidates can occur due to resignation, death, ineligibility, dismissal from a political party, or a decision by an authorized institution. However, the practice of cancellation in the 2024 Election still raises legal issues, particularly related to legal uncertainty and the potential weakening of the principle of majority vote. The open proportional representation system, which places voters as the primary determinant of elected candidates, also has the potential to be disrupted if the cancellation is not carried out transparently and accountably. Furthermore, the cancellation of the determination of elected candidates can undermine public trust in the election process and shift the meaning of popular sovereignty. Therefore, regulatory strengthening and policy harmonization are needed to ensure that the cancellation of the determination of elected candidates remains in line with the principles of constitutional democracy in Indonesia.